2016
DOI: 10.1080/02701367.2016.1182113
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Movement Skills in Obese Children With and Without Prader-Willi Syndrome

Abstract: Motor proficiency is very poor in OB-PWS, in particular for gross motor skills. Physical, neurological, and developmental characteristics inherent to the syndrome may explain this low performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The low prevalence of PWS (1 in 10,000 to 1 in 30,000) increases the difficulty of completing group-based PA interventions with this population [1]. The emotional characteristics (age-inappropriate temper tantrums, stubbornness, skin picking, impulsivity, ritualistic, and repetitive behaviors) [1], poor motor proficiency [11], and intellectual challenges prevalent in youth with PWS [12] argue for tailored interventions. Therefore, we designed a 24-week home-based intervention [13] to be delivered by parents using a PA curriculum with preplanned sessions comprising console-based interactive games and goal-oriented, age-appropriate playground games.…”
mentioning
confidence: 99%
“…The low prevalence of PWS (1 in 10,000 to 1 in 30,000) increases the difficulty of completing group-based PA interventions with this population [1]. The emotional characteristics (age-inappropriate temper tantrums, stubbornness, skin picking, impulsivity, ritualistic, and repetitive behaviors) [1], poor motor proficiency [11], and intellectual challenges prevalent in youth with PWS [12] argue for tailored interventions. Therefore, we designed a 24-week home-based intervention [13] to be delivered by parents using a PA curriculum with preplanned sessions comprising console-based interactive games and goal-oriented, age-appropriate playground games.…”
mentioning
confidence: 99%
“…Lower values of flexibility (~42%) and muscle strength (~50%–70%) were shown in adult PWS patients compared to normal‐weight and overweight/obese age‐matched controls . In children and adolescents with PWS aged 8‐16 years, lower levels (~40%) of motor proficiency (co‐ordination, agility, speed, muscular strength and balance) were also reported in comparison to children with obesity but without PWS …”
Section: Resultsmentioning
confidence: 94%
“…A total of 483 studies were identified, of which 447 did not meet the inclusion criteria. Twenty-two studies, 10,15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] whose details are summarized in Tables 2 and 3 Mullins (1987)…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations